Comparative Study of Temporalis Fascia Graft versus Cartilage Shield Tympanoplasty in Chronic Otitis Media - Mucosal Type - Shrestha, Kumar; Paduel, Dhundi Raj; Bhandari, Shama; Mahaseth, Subhash Chandra (Journal of Nepalgunj Medical College, 2022)
Introduction: Tympanoplasty is the procedure of choice for surgical correction of tympanic membrane perforation triggered by either chronic otitis media or trauma. Various types of autologous grafts have been used to close tympanic membrane perforations among which temporalis fascia and tragal cartilage are preferred, due to their anatomic proximity, ease of harvesting and suppleness.Aims: To compare clinical and audiological outcomes of type 1 tympanoplasty where temporalis fascia and tragal cartilage were used as the graft material.Methods: A prospective study was conducted on 50 patients of ages ranging from 10 to 50 years with Chronic Otitis Media - Mucosal. All the patients underwent type 1 tympanoplasty and were categorized into Group-A (Temporalis fascia graft) and Group-B (Cartilage graft), each group comprising of 25 patients. Graft uptake rate, hearing gain and air bone gap closure were compared between the groups in 4 and 8 weeks after surgery.Results: Out of total 50 patients, 20 were male and 30 were female. The average age of the patients was 28.20 years. The total hearing gain in the whole series was 14.94 dB while the total air bone gap closure was 14.78 dB respectively. The difference between pre and post-operative hearing was statistically significant for both air bone gap and air conduction, (P